Determinants of Firm Performance: An Empirical Evidence from Construction Industry in Indonesia - Dhiraj Kelly Sawlani , Idris Gautama So , Asnan Furinto , Mohammad Hamsal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The construction industry is the 4th largest contributing industry to gross domestic product in 2016 in Indonesia. However, its’ growth is slowing down recently because of the companies’ low competitiveness that causes production inefficiency. Despite the urgency for a comprehensive solution to increase its productivity, research in this area is still lacking. This study aims to examine the development and application of electronic customer relationship management (e-CRM) theory, project innovation (PI), project organizational culture (BO), and dynamic capabilities (KD) in increasing competitive advantage (KB), and its implications for business performance (KP), moderated by the size of construction companies in Indonesia.By collaborating with PT BCI Asia for data collection, at least 200 responses are targeted to collect from online questionnaires and analyzed by structural equation modeling (SEM). We found that (1) there is a significant influence of e-CRM, PI, and KD on KB; (2) there is an influence of PI, BO, and KD on KP, while e-CRM has no significant effect; (3) there is a significant influence of KB on KP in Indonesian construction firm; (4) KB mediates the influence of e-CRM, PI, BO, and KD on KP; and (5) firm size moderates the effect of KB on KP.